If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -4x + 6 = 0 + -5x Reorder the terms: 6 + -4x = 0 + -5x Remove the zero: 6 + -4x = -5x Solving 6 + -4x = -5x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '5x' to each side of the equation. 6 + -4x + 5x = -5x + 5x Combine like terms: -4x + 5x = 1x 6 + 1x = -5x + 5x Combine like terms: -5x + 5x = 0 6 + 1x = 0 Add '-6' to each side of the equation. 6 + -6 + 1x = 0 + -6 Combine like terms: 6 + -6 = 0 0 + 1x = 0 + -6 1x = 0 + -6 Combine like terms: 0 + -6 = -6 1x = -6 Divide each side by '1'. x = -6 Simplifying x = -6
| 8n=51+3 | | 3x+10=-22-5 | | 270=(13+2x)x(9+2x) | | 3w^2-365x+8550=0 | | (5y+p)+10y=0 | | 5x+2=4x+24 | | (6P+3)= | | 20x+2=20x+2 | | 8n=51-3 | | 9x-(7x-7)=21 | | 4x+2=4x+22 | | N=yp | | 8(x^2-x+8)=0 | | (3x^2-4x+17)+(7x^2+7x-75)= | | 4+2p=6p-20 | | 75x+35x-10=0 | | 5p+6-2p-4=17 | | 0.0001x+2=4x+2 | | 7(x-4)-4x=2x-3-(5-6x) | | 1234x+2=4x-99 | | 4(x-5)=(5-x)4 | | (2v)-4=8 | | 2c-16=10c | | 24x+2=4x+-8 | | b^2=8b-22 | | 9x+2=4x+0.1 | | 2.3-5y=-37 | | X(n+3)=3n+9 | | -log(x)=7.5 | | X(n+3)=3n+8 | | 45x-16=-20x+116 | | 1x+2=4x+3 |